Cyanoacrylate Vein Glue and Allergy - A Real Problem ? - Saphenion, Dr. Ulf Th. Zierau (International Journal of Innovative Research in Medical Science, 2019)
Vein Glue and allergy - is there a significant risk? In a few specialist comments and articles by phlebologically active colleagues is repeatedly warned against the emergence of an allergy to the cyanoacrylate used in the vein glue. Reason enough for us to compare our own experience with the use of the vein adhesive with the worldwide specialist literature.